Morphology and genealogy of structural defects in vacuum ion-plasma coatings - O. V. Kudryakov; V. N. Varavka; I. Yu. Zabiyaka; E. A. Yadrets; V. P. Karavaev (Advanced Engineering Research, 2020)
Introduction. The main work objective is systematization and analysis of structural defects of vacuum ion-plasma coatings; on this basis, their classification principles are developed and given in the paper. Another important part of the work is the experimental study on one of the specific defects of coatings, which the authors propose to call “defect of substructural origin”.Materials and Methods. PVD coatings of various nitride and metal systems 1.5-9.0 μm thick were used as an object of the research. Coatings were applied in vacuum installations using arc and magnetron evaporators. The research results were obtained by high resolution electron microscopy, energy dispersive analysis and indentation.Results. Various types of defects in ion-vacuum coatings are presented as the research results. They include discontinuities, deformation of crystallites, and structural inhomogeneity. The principles of their systematization are validated. It is proposed to classify defects into droplet, substructural, and growth defects (depending on the causes of their nucleation), as well as regular and stochastic ones (depending on their distribution in the coating volume). The study of “substructural defects”, classified by the authors as stochastic, is given special consideration. These micrometric defects are shaped like a cylinder with a conical “head”. Their main axle is oriented perpendicular to the surface of the coating. They can be “extruded” (tore away) by the coating. The paper validates the dislocation mechanism of their nucleation and the helicoid growth principle. Conclusions. The inference is summarized that the proposed systematization of defects in ion-plasma coatings has the character of an intermediate result of research in this scientific area. At this, the “substructural defects” do not have a fatal effect on the structure and properties of the coating due to a small size.